THE EFFECTIVENESS OF JOURNALISTIC QUESTIONS METHOD IN WRITING RECOUNT TEXT AT TENTH GRADE STUDENTS OF MA AL-HIDAYAH SUMBAKELING PANCALANG KUNINGAN - Zesy Alvisa; Sumadi sumadi; Siti Luruh Ayu Noerjanah (IAIN Syekh Nurjati Cirebon, 2018)
The researcher chooses this title because she found students who have difficulties to start writing at tenth grade students in MA Al- Hidayah Sumbakeling. Therefore, this study aimed to find out the effectiveness of Journalistic questions method in teaching writing recount text at tenth grade students of MA Al-Hidayah Sumbakeling Pancalang Kuningan. The method used in this research was a quantitative research and the design was a quasi-experiment. The sample of this research was two classes which was divided into experimental class and controlled class. X-A as the experimental class consist of 22 students and X-B as the controlled class consist of 20 students.Â The experimental class was taught using Journalistic questions method while the controlled class was taught without using the Journalistic questions method. In collecting data, the researcher conducted a writing test which was divided into test (pre-test and post-test) and documentation. The data collected were analyzed by using SPSS v.20 and t-test. According to the result of statistical calculation, it could be seen that to was 65.91 and tt was 1.68. It means that to was higher than tt (to > tt). Thus, the alternative hypothesis (Ha) is accepted and null hypothesis (H0) is rejected. In conclusion, using Journalistic questions method is effective on studentsâ€™ writing skill of recount text.